The fourth aim of the University of the Philippines System a recommendation - Martires, Conception Rodil (Education quarterly.)
The significance of human development as an aim in education was brought out to the fore by Manalang, "what is important is not to survive the comfortable way but to survive the human way." The Human Settlements Program of the present administration is a manifestation of the credence place on the dignity of human being. The university should start with the person of the student which is its raison d'etre. The U.P. graduate who is also humanly developed, is a greater asset than the one who is only academically and professionally prepared. the human individual relates humanely to others after having been made perceptive and responsible to himself and others and effective with himself and others. He is the best antidote to a dehumanized Philippine mankind. He is the best contribution of the U.P. System to the development of the country.